"A Treatise from Tafsir by Muhammad al-Alwānī (d. 1096 AH): Interpretation of 'That you not worship except Allah' – Sūrat Hūd, 26: A Study and Edition" (Journal of the College of Basic Education, 2025)
This research is a study and investigation of an important manuscript in the field of interpretation. Its subject revolves around the interpretation of the verse "that you worship none but God" from Surat Hud. Al-Wani addresses several opinions regarding the meaning of "an" in this noble verse. He points to the opinion of the virtuous Abu al-Su'ud, who believes that "an" here is a verbal noun, while others object to him, relying on what is stated in "Mughni al-Labib," which explains that "an" can be prohibitive or verbal noun.Al-Wani elaborates on these objections, clarifying the difference between "an" being prohibitive or verbal noun, and citing interpretations from scholars such as al-Baydawi and Sa'di Jalabi. He also discusses the issue of the non-dropping of the letter "nun" in the present tense, explaining that this relates to whether "an" is a verbal noun or a verbal noun. In concluding the text, Al-Wani emphasizes the importance of understanding the multiple meanings of words, noting that interpretation should focus on meanings rather than just linguistic form. He also points out the need to reflect on the opinions of scholars and acknowledge the diversity of opinions in interpreting Quranic texts.